Aspartate aminotransferase from the anctarctic bacterium Pseudolteromonas haloplanktis TAC 125. Clonong, expression, properties, and molecular modelling. - BIROLO, LEILA; TUTINO, MARIA LUISA; FONTANELLA, BIANCA; SANNIA, GIOVANNI; VINCI, FLORIANA; MARINO, GENNARO; GERDAY C; MAINOLFI K; PASCARELLA S (European Journal of Biochemistry, 2000)
The gene encoding aspartate aminotransferase from the psychrophilic bacterium Pseudoalteromonas haloplanktis TAC 125 was cloned, sequenced and overexpressed in Escherichia coli. The recombinant protein (PhAspAT) was characterized both at the structural and functional level in comparison with the E. coli enzyme (EcAspAT), which is the most closely related (52% sequence identity) bacterial counterpart. PhAspAT is rapidly inactivated at 50 degrees C (half-life = 6.8 min), whereas at this temperature EcAspAT is stable for at least 3 h. The optimal temperature for PhAspAT activity is approximate to 64 degrees C, which is some 11 degrees C below that of EcAspAT. The protein thermal stability was investigated by following changes in both tryptophan fluorescence and amide ellipticity; this clearly suggested that a first structural transition occurs at approximate to 50 degrees C for PhAspAT. These results agree with the expected thermolability of a psychrophilic enzyme, although the observed stability is much higher than generally found for enzymes isolated from cold-loving organisms. Furthermore, in contrast with the higher efficiency exhibited by several extracellular psychrophilic enzymes, both k(cat) and k(cat)/K-m of PhAspAT are significantly lower than those of EcAspAT over the whole temperature range. This behaviour possibly suggests that the adaptation of this class of endocellular enzymes to a cold environment may have only made them less stable and not more efficient. The affinity of PhAspAT for both amino-acid and 2-oxo-acid substrates decreases with increasing temperature. However, binding of maleate and 2-methyl-L-aspartate, which both inhibit the initial steps of catalysis, does not change over the temperature range tested. Therefore, the observed temperature effect may occur at any of the steps of the catalytic mechanism after the formation of the external aldimine. A molecular model of PhAspAT was constructed on the basis of sequence homology with other AspATs. Interestingly, it shows no insertion or ...